2022
DOI: 10.4102/safp.v64i1.5527
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of final year undergraduate nursing students about HIV and AIDS in Eswatini

Abstract: This study contributed by providing knowledge of undergraduate nursing students' HIV and AIDS training and management of PLWHA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…However, the former study used convenient sampling which might have affected the overall results. In Eswatini [22] found that 87.1% of final year undergraduate nursing students knew that HIV and AIDS were not curable. However, a nonprobability convenience sampling method was also used which could have impacted on the overall results.…”
Section: Resultsmentioning
confidence: 99%
“…However, the former study used convenient sampling which might have affected the overall results. In Eswatini [22] found that 87.1% of final year undergraduate nursing students knew that HIV and AIDS were not curable. However, a nonprobability convenience sampling method was also used which could have impacted on the overall results.…”
Section: Resultsmentioning
confidence: 99%
“…Temuan yang tidak sejalan dengan hasil penelitian ini telah ditemukan dibeberapa negara lain, dimana hasil penelitian menunjukkan bahwa sarjana keperawatan pengetahuan siswa relatif rendah tentang HIV dan AIDS di seluruh dunia (Dlamini et al, 2022). Pengetahuan keperawatan sarjana siswa dilaporkan sangat tinggi dalam studi lain (Ngcobo & Mchunu, 2019) dan sedang atau tidak memadai dalam beberapa penelitian (Dlamini et al, 2022).…”
Section: Latar Belakangunclassified